The comparison between motor imagery and verbal rehearsal on the learning of sequential movements - Saimpont, Arnaud; Lafleur, Martin F.; Malouin, Francine; Richards, Carol L.; Doyon, Julien; Jackson, Philip L. (Frontiers in Human Neuroscience, 2013)
Mental practice refers to the cognitive rehearsal of a physical activity. It is widely used by athletes to enhance their performance and its efficiency to help train motor function in people with physical disabilities is now recognized. Mental practice is generally based on motor imagery (MI) i.e. the conscious simulation of a movement without its actual execution. It may also be based on verbal rehearsal (VR) i.e. the silent rehearsal of the labels associated with an action. In this study, the effect of MI training or VR on the learning and retention of a foot-sequence task was investigated. Thirty right-footed subjects, aged between 22 and 37 years old (mean: 27.4±4.1 years) and randomly assigned to one of three groups, practiced a serial reaction time task involving a sequence of three dorsiflexions and three plantar flexions with the left foot. One group (n=10) mentally practiced the sequence with MI for five weeks, another group (n=10) mentally practiced the sequence with VR of the foot positions for the same duration, and a control group (n=10) did not practice the sequence mentally. The time to perform the practiced sequence as well as an unpracticed sequence was recorded before training, immediately after training and six months after training (retention). The main results showed that the speed improvement after training was significantly greater in the MI group compared to the control group and tended to be greater in the VR group compared to the control group. The improvement in performance did not differ in the MI and VR groups. At retention, however, no difference in response times was found among the three groups, indicating that the effect of mental practice did not last over a long period without training. Interestingly, this pattern of results was similar for the practiced and non-practiced sequence. Overall, these results suggest that both MI training and VR help to improve motor performance and that mental practice may induce non-specific effects.